Evaluasi Dan Perbaikan Proses Bisnis Menggunakan Metode Business Prosess Improvement (BPI) (Studi Kasus Pada Divisi Sekretaris dan Keuangan PT. Kerta Betamala Trans) - Muhammad Iqbal; Nanang Yudi Setiawan; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT. Kerta Betamala Trans is a company engaged in freight forwarding services in Indonesia. PT Kerta Betamala Trans has divisions to ensure business activities run accordingly, so that its business objectives can be achieved. Among them in the division at PT. Kerta Betamala Trans is Secretary and Finance. The problem often arises that there is an improper recitation data record. Because every six months there are 25% of 15 employees whose data records are not appropriate. This causes the recording of company data to experience a discrepancy in the recording data and harm the company in financial terms. Because of this, it is necessary to evaluate and improve business prosesses. Functional decomposition of value chain anaIysis is done to get the main business prosesses and get 4 main business prosesses. Then an evaluation of the employee payroll business prosess is carried out using the FaiIure Mode and Effect AnaIysis (FMEA) method, after an evaluation has been made the root of the problem is an error because the attendance data is invalid when calculating salaries. After the evaluation, treatment was carried out with tools StreamIining from Business Prosess Improvement (BPI) which aimed to get business prosess recommendations. From the StreamIining results obtained from the calculation of attendance which was originally manual using the attendance book replaced to attendance using biometric attendance (fingerprint) and get the biggest difference from the results of the simulation simulation prosess found in the employee payroll business prosess with a percentage increase of 70.52%.